Investigation of the Behavior of Output Variables for Arbitrary Inputs to high Voltage Direct Current Power System Modeling Using Lyapunov Function Nonlinear Control Model - Goughari, Rohollah S.; Shahbazzadeh, Mehdi J.; Eslami, Mahdieh (Recent Advances in Electrical & Electronic Engineering, 2021)
Background: Until now, a variety of proportional integral controllers and local controllers and predictive controller models have been used to stabilize VSC-HVDC transmission lines. One of the disadvantages of a linear model predictive control is that it is difficult and time consuming to adjust it for times when the disturbance entering the system is sudden. The goal is to monitor and take appropriate action to balance power and eliminate voltage or current that has exceeded the allowable limit. Methods: The way it works is that first, the DC current and the measured voltage of converter power source (VSC) is sup-plied based on various factors, and then the converters slowly begin to track the desired reference value, and this continues until the power sources are adjusted according to current and voltage limits. Results: To achieve this goal, this paper examines recent articles on the modeling of VSC-HVDC power transmission systems and a comprehensive model has been chosen that has not been published for several months since its publication. Next, to control the selected model, the combined control strategy of nonlinear predictive based on the Lyapunov function is used to ensure the stability of the system. Conclusion: The results of the implementation of this control strategy on the HVDC power transmission system model in MATLAB soft-ware express the ability of this controller to track the reference input values.
Keywords: model predictive control